(untitled) (Bangladesh Agronomy Journal, 2020)
A pot experiment was conducted with five selected rapeseed/mustard genotypes (BJDH-11, BJDH-12, BJDH-20, BARI Sarisha-14, and BARI Sarisha-16) under two sowing dates (November 20 and December 20) for evaluating their responses to sowing date induced high temperature stress during rabi season of 2017-18. Sowing dates induced temperature variability showed remarkable changes in pheonlogy, leaf area, leaf chlorophyll content, dry matter production and seed yield. Although December 20 sown crop received lower temperatures (minimum 9.8 to 13.2 and maximum 22.6 to 27oC) than November 20 sown crop (minimum 14.8 to 16.4 and maximum 21 to 27.2oC) at flowering but reverse was found at grain development stage. Grain development stage of November 20sown crop received lower temperatures (minimum 8.2 to 13.2 and maximum 24.1 to 27 oC) while December 20 sown crop received higher temperatures at grain development stage (minimum 8.2 to 18 and maximum 22.6 to 32.5oC).As a result December 20 sown crop matured earlier (6 to 9 days) than November 20 sown crop. Leaf area/plant was higher in December 20 sown crops compared to November 20 sown but total dry matter production was more or less same in both the sowing dates. Leaf chlorophyll content did not show any remarkable variation due to variation in sowing dates. However, antioxidant activity like Catalyse (CAT), Peroxidase (POD) Ascorbate peroxidase (APX) and Malondial dehyde (MDA) were found higher in December 20 sown crops than that of November 20sown. Higher activity of APX, POD and CAT with lower activity of MDA indicates comparatively high temperature tolerant genotype. Among the genotypes APX, POD and CAT activity were found higher with lower activity of MDA in BJDH-11 and BJDH-20 and these genotypes also gave higher yield than others. On the basis of growth parameters, antioxidant activity and seed yield of genotype BJDH-11 and BJDH-20 could be select as terminal high temperature tolerance genotypes. Bangladesh Agron. J. 2019, 22(1): 47-56